The Influence of Organizational Justice and Employee Engagement on Turnover Intention Through Job Satisfaction as a Simple Mediator - Sudarta, Sudarta; Urfina, Yasyifa Dian; Candra, Candra; Naim, Muhammad; Wirastomo, Handoyo; Khalik, Abdul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the effect of organizational justice and employee engagement on turnover intention through job satisfaction as a simple mediator at Muhammadiyah University of Mataram. Using a quantitative causal-comparative approach, data were collected from 94 contract lecturers selected through the Slovin formula. The questionnaire consisted of 20 items covering four variables: organizational justice, employee engagement, job satisfaction, and turnover intention, measured on a five-point Likert scale. Data were analyzed using the SmartPLS 4 software to test the measurement and structural models. The results indicate that organizational justice has no significant effect on job satisfaction (p = 0.444) and turnover intention (p = 0.229). Employee engagement has a significant negative effect on job satisfaction (p = 0.030) and a significant negative effect on turnover intention (p = 0.009). Meanwhile, job satisfaction does not have a significant effect on turnover intention (p = 0.966), and mediation testing shows that job satisfaction does not mediate the relationship between organizational justice or employee engagement and turnover intention. These findings suggest that employee engagement is the dominant factor influencing turnover intention, while organizational justice and job satisfaction play limited roles. The study recommends future research to include additional mediating variables such as organizational commitment or leadership support to provide a more comprehensive understanding of turnover determinants in educational institutions.